Copper nanowire and its preparation method and application

By controlling the molar ratio and reaction conditions of the raw materials during the preparation of copper nanowires, copper nanowires with a wire diameter of 12-35nm and a wire length of 10-40μm were successfully prepared, which solved the problem of insufficient wire diameter and length-to-diameter ratio of copper nanowires in the prior art, and achieved higher performance indicators and simpler processes.

CN115156522BActive Publication Date: 2025-03-18NUOVO FILM SUZHOU CHINA INC
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202210892503.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-07-27
Publication Date
2025-03-18
Estimated Expiration
2042-07-27

AI Technical Summary

Technical Problem

The existing copper nanowire line diameter to aspect ratio cannot meet the needs of flexible conductive materials and transparent conductive films.

Method used

By mixing copper sources, chlorine-containing compounds, bromine-containing compounds, protective agents, polyols and reducing agents, synthesis reactions and separation treatments, copper nanowires with a wire diameter of 12-35 nm and a wire length of 10-40 μm are prepared.

Benefits of technology

The ultra-refining and aspect ratio of copper nanowires have been achieved, which can better meet the requirements of flexible conductive materials and transparent conductive films. At the same time, the reaction temperature is low, the process is simple, and it is suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115156522B_ABST
    Figure CN115156522B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of nanomaterials, and specifically relates to a copper nanowire and a preparation method and application thereof. The preparation method comprises: (1) mixing a copper source, a chlorine-containing compound, a bromine-containing compound, a protective agent, a polyol and a reducing agent to obtain a mixed solution; (2) subjecting the mixed solution to a synthetic reaction to obtain a product system; (3) separating the product system, and post-treating the separated solid phase to obtain a copper nanowire. To achieve the synthesis of ultrafine copper nanowires, the diameter of the product can be controlled by controlling the molar ratio of chlorine and bromine in the raw materials during the preparation process. The diameter of the obtained copper nanowire can be controlled to be 12-35nm, and the length of the wire can be controlled to be 10-40μm. The reaction temperature is low, the preparation process is simple, it is conducive to large-scale production, and energy consumption is saved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of nanomaterials, and in particular relates to a copper nanowire and a preparation method and application thereof. Background Art

[0002] Flexible electronic devices are one of the hot areas of academic and industrial attention. Electrodes with good flexibility and conductivity are the basis of flexible electronic devices, among which flexible transparent electrodes are the most important. Flexible transparent electrodes based on metal nanowires have become an important option to replace traditional indium tin oxide (ITO) electrodes due to their advantages such as high performance, low cost and easy large-scale production. In order to obtain electrodes with low haze, high transmittance and high conductivity, the metal nanowires, one of the raw materials for their preparation, should have an ultra-fine diameter and a large aspect ratio. Summary of the invention

[0003] Aiming at the problem that the existing copper nanowires cannot meet the requirements of the flexible conductive material and transparent conductive film field for thin wire diameter and large aspect ratio of nano copper wires in terms of wire diameter and aspect ratio, the present invention provides a copper nanowire and a preparation method and application thereof.

[0004] In order to achieve the above object, the present invention provides a first aspect of a method for preparing copper nanowires, the method comprising:

[0005] (1) mixing a copper source, a chlorine-containing compound, a bromine-containing compound, a protective agent, a polyol and a reducing agent to obtain a mixed solution;

[0006] (2) subjecting the mixed solution to a synthesis reaction to obtain a product system;

[0007] (3) separating the product system and post-treating the separated solid phase to obtain copper nanowires.

[0008] The second aspect of the present invention provides copper nanowires prepared by the method described in the first aspect, wherein the copper nanowires have a diameter of 12-35 nm and a length of 10-40 μm.

[0009] The third aspect of the present invention provides the use of the copper nanowires described in the second aspect in flexible conductive materials and transparent conductive films.

[0010] Through the above technical solution, the present invention has the following beneficial effects:

[0011] (1) Based on the polyol system, ultrafine copper nanowires were synthesized under normal pressure. The diameter of the wire was regulated by controlling the molar ratio of chlorine to bromine in the raw materials. The diameter of the copper nanowires can be controlled to be 12-35nm and the length to be 10-40μm, which can better meet the requirements for the use of copper nanowires in flexible conductive materials and transparent conductive films.

[0012] (2) The reaction temperature is low and the preparation process is simple, which is conducive to mass production and reduces energy consumption. BRIEF DESCRIPTION OF THE DRAWINGS

[0013] The accompanying drawings are used to provide a further understanding of the present invention and constitute a part of the specification. Together with the following specific embodiments, they are used to explain the present invention but do not constitute a limitation of the present invention. In the accompanying drawings:

[0014] Figure 1 This is a transmission electron microscope image of the copper nanowires prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0015] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0016] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.

[0017] A first aspect of the present invention provides a method for preparing copper nanowires, the method comprising:

[0018] (1) mixing a copper source, a chlorine-containing compound, a bromine-containing compound, a protective agent, a polyol and a reducing agent to obtain a mixed solution;

[0019] (2) subjecting the mixed solution to a synthesis reaction to obtain a product system;

[0020] (3) separating the product system and post-treating the separated solid phase to obtain copper nanowires.

[0021] According to the present invention, the copper source is preferably a copper salt, and a conventional copper source for preparing metal nanowires in the art can be selected. Preferably, the copper source can be selected from at least one of copper nitrate, copper carboxylate, copper sulfate, copper acetylacetonate, copper acetate and copper chloride.

[0022] According to the present invention, the chlorine-containing compound can be selected from at least one of cetyltrimethylammonium chloride, octadecyltrimethylammonium chloride, tetrapropylammonium chloride and tetrabutylammonium chloride, preferably cetyltrimethylammonium chloride.

[0023] According to the present invention, the bromine-containing compound can be selected from at least one of cetyltrimethylammonium bromide, octadecyltrimethylammonium bromide, tetrapropylammonium bromide and tetrabutylammonium bromide, preferably cetyltrimethylammonium bromide.

[0024] According to the present invention, the protective agent is preferably an organic protective agent, which plays a "capping" role during the synthesis reaction. Preferably, the protective agent can be selected from at least one of polyvinyl pyrrolidone, nitrogen methyl pyrrolidone, hexadecylamine and polyvinyl alcohol, preferably polyvinyl pyrrolidone.

[0025] According to the present invention, the polyol is used as a solvent in the reaction system and also has a certain reducing effect. It can be selected from conventional polyol solvents for preparing metal nanowires in the art. Preferably, the polyol can be selected from at least one of ethylene glycol, propylene glycol and glycerol.

[0026] According to the present invention, the use of a reducing agent with strong reducing properties can reduce the reaction temperature and shorten the reaction time. Preferably, the reducing agent can be selected from at least one of hydrazine hydrate, potassium borohydride, sodium borohydride and ferric sulfate, preferably hydrazine hydrate.

[0027] According to the present invention, in step (1), the feed amount of each raw material is such that, in the mixed solution, the molar ratio of copper ion: chloride ion: reducing agent: protecting agent is 1: (0.01-1): (0.1-3): (1-8), preferably 1: (0.05-0.3): (1-3): (4-6);

[0028] Furthermore, in the mixed solution, the molar ratio of chloride ion:bromide ion is (0.25-4):1, and more preferably (0.5-2):1.

[0029] In the present invention, the diameter of the copper nanowire product can be regulated by controlling the molar ratio of chloride ions to bromide ions provided by the reaction raw materials, thereby achieving the synthesis of ultrafine copper nanowires, the diameter of which can be controlled to be 12-35nm and the length of which is 10-40μm.

[0030] According to the present invention, in step (1), preferably, the weight ratio of the polyol to the protective agent is (60-80):1.

[0031] According to the present invention, in step (1), the raw materials can be mixed in a conventional manner, and the present invention has no particular limitation on this. In a preferred embodiment of the present invention, the copper source, the chlorine-containing compound, the bromine-containing compound, the protective agent and the polyol can be mixed first, so that the raw materials are fully dissolved in the polyol, and then the reducing agent is added for mixing to obtain a uniform mixed solution.

[0032] According to the present invention, in step (2), the mixed solution undergoes a synthesis reaction under heating conditions. During the reaction, copper ions are first reduced in a polyol system, and then selectively grow under the action of a protective agent, chloride ions and bromide ions to obtain copper nanowires. Preferably, the conditions of the synthesis reaction include: a temperature of 120-180°C, preferably 140-150°C; a time of 30-300 min, preferably 240-300 min.

[0033] According to the present invention, the method further comprises: before the synthesis reaction, the mixed solution is subjected to a heating treatment under an inert atmosphere to remove water and oxygen. During the operation, an inert gas may be introduced into the mixed solution and heated to discharge water and oxygen from the mixed solution. Preferably, the conditions for the heating treatment include: a temperature of 135-150° C. and a time of 1-10 min.

[0034] In the present invention, the inert gas may be nitrogen, helium, argon or other inert gases, preferably nitrogen.

[0035] According to the present invention, in step (2), the product system is a mixture containing solid and liquid phases, wherein the solid phase is the synthesized copper nanowire product.

[0036] According to the present invention, in step (3), the separation may be carried out by a conventional solid-liquid separation method, which is not particularly limited in the present invention. For example, centrifugal separation, suction filtration, etc. may be used.

[0037] According to the present invention, in step (3), the post-treatment includes washing and drying performed in sequence.

[0038] In the present invention, unreacted raw materials attached to the surface of the solid phase product are removed by washing, and the washing liquid used is preferably at least one of water, ethanol and ethyl acetate, and more preferably water.

[0039] In the present invention, there is no particular limitation on the drying as long as the purpose of solid phase drying after washing can be achieved.

[0040] The second aspect of the present invention provides copper nanowires prepared by the method described in the first aspect, wherein the copper nanowires have a diameter of 12-35 nm and a length of 10-40 μm.

[0041] The third aspect of the present invention provides the use of the copper nanowires described in the second aspect in flexible conductive materials and transparent conductive films.

[0042] The present invention will be described in detail below by way of examples. In the following examples and comparative examples,

[0043] The diameter of the copper nanowires was measured by transmission electron microscopy, and the length of the copper nanowires was measured by statistics of optical microscopy images.

[0044] Unless otherwise specified, all materials used are common commercially available products.

[0045] Example 1

[0046] (1) 4 g of copper nitrate trihydrate, 0.75 g of hexadecyltrimethylammonium chloride, 1.7 g of hexadecyltrimethylammonium bromide, and 8 g of polyvinylpyrrolidone PVP-K90 were placed in a three-necked round-bottom flask filled with ethylene glycol, stirred until completely dissolved, and then 1 ml of hydrazine hydrate was added, and stirring was continued to obtain a uniform mixed solution;

[0047] The feed amounts of the above raw materials satisfy the following conditions: in the mixed solution, the molar ratio of copper ion: chloride ion: hydrazine hydrate: polyvinyl pyrrolidone PVP-K90 is 1:0.14:1.2:4.4; the molar ratio of chloride ion: bromide ion is 0.5:1; the weight ratio of ethylene glycol: polyvinyl pyrrolidone PVP-K90 is 68:1;

[0048] (2) introducing nitrogen into the mixed solution, heating the mixed solution to 140° C., and maintaining the temperature for 5 min to fully remove water and oxygen, then stopping the nitrogen flow; maintaining 140° C., and conducting a synthesis reaction at the temperature for 240 min, then stopping heating and naturally cooling to room temperature to obtain a product system;

[0049] (3) The product system was mixed and diluted with water at a volume ratio of 1:1, and then centrifuged at 3600 rpm for 30 min. The upper clear liquid was poured off, and the lower solid phase precipitate was washed with deionized water and ethanol and dried to obtain copper nanowires (denoted as S1).

[0050] Figure 1 This is a transmission electron microscope image of S1, showing the successful preparation of copper nanowire products.

[0051] The wire diameter and wire length parameters of S1 are shown in Table 1.

[0052] Example 2

[0053] (1) 4 g of copper nitrate trihydrate, 0.75 g of hexadecyltrimethylammonium chloride, 0.85 g of hexadecyltrimethylammonium bromide, and 8 g of polyvinylpyrrolidone PVP-K90 were placed in a three-necked round-bottom flask filled with ethylene glycol, stirred until completely dissolved, and then 1 ml of hydrazine hydrate was added, and stirring was continued to obtain a uniform mixed solution;

[0054] The feed amounts of the above raw materials satisfy the following conditions: in the mixed solution, the molar ratio of copper ion: chloride ion: hydrazine hydrate: polyvinyl pyrrolidone PVP-K90 is 1:0.14:1.2:4.4; the molar ratio of chloride ion: bromide ion is 1:1; the weight ratio of ethylene glycol: polyvinyl pyrrolidone PVP is 68:1;

[0055] (2) introducing nitrogen into the mixed solution, heating the mixed solution to 140° C., and maintaining the temperature for 5 min to fully remove water and oxygen, then stopping the nitrogen flow; maintaining 140° C., and conducting a synthesis reaction at the temperature for 240 min, then stopping heating and naturally cooling to room temperature to obtain a product system;

[0056] (3) The product system was mixed and diluted with water in a volume ratio of 1:1, and then centrifuged at 3600 rpm for 30 min. The upper clear liquid was poured off, and the lower solid phase precipitate was washed with deionized water and ethanol and dried to obtain copper nanowires (denoted as S2).

[0057] The wire diameter and wire length parameters of S2 are shown in Table 1.

[0058] Example 3

[0059] (1) 4 g of copper nitrate trihydrate, 0.75 g of hexadecyltrimethylammonium chloride, 0.425 g of hexadecyltrimethylammonium bromide, and 8 g of polyvinylpyrrolidone PVP-K90 were placed in a three-necked round-bottom flask filled with ethylene glycol, stirred until completely dissolved, and then 1 ml of hydrazine hydrate was added, and stirring was continued to obtain a uniform mixed solution;

[0060] The feed amounts of the above raw materials satisfy the following conditions: in the mixed solution, the molar ratio of copper ion: chloride ion: hydrazine hydrate: polyvinyl pyrrolidone PVP-K90 is 1:0.14:1.2:4.4; the molar ratio of chloride ion: bromide ion is 2:1; the weight ratio of ethylene glycol: polyvinyl pyrrolidone PVP is 68:1;

[0061] (2) introducing nitrogen into the mixed solution, heating the mixed solution to 140° C., and maintaining the temperature for 5 min to fully remove water and oxygen, then stopping the nitrogen flow; maintaining 140° C., and conducting a synthesis reaction at the temperature for 240 min, then stopping heating and naturally cooling to room temperature to obtain a product system;

[0062] (3) The product system was mixed and diluted with water at a volume ratio of 1:1, and then centrifuged at 3600 rpm for 30 min. The upper clear liquid was poured off, and the lower solid phase precipitate was washed with deionized water and ethanol and dried to obtain copper nanowires (denoted as S3).

[0063] The wire diameter and length parameters of S3 are shown in Table 1.

[0064] Example 4

[0065] (1) 4 g of copper nitrate trihydrate, 0.75 g of hexadecyltrimethylammonium chloride, 3.4 g of hexadecyltrimethylammonium bromide, and 8 g of polyvinylpyrrolidone PVP-K90 were placed in a three-necked round-bottom flask filled with ethylene glycol, stirred until completely dissolved, and then 1 ml of hydrazine hydrate was added, and stirring was continued to obtain a uniform mixed solution;

[0066] The feed amounts of the above raw materials satisfy the following conditions: in the mixed solution, the molar ratio of copper ion: chloride ion: hydrazine hydrate: polyvinylpyrrolidone PVP-K90 is 1:0.14:1.2:4.4; the molar ratio of chloride ion: bromide ion is 0.25:1; the weight ratio of ethylene glycol: polyvinylpyrrolidone PVP is 68:1;

[0067] (2) introducing nitrogen into the mixed solution, heating the mixed solution to 140° C., and maintaining the temperature for 5 min to fully remove water and oxygen, then stopping the nitrogen flow; maintaining 140° C., and conducting a synthesis reaction at the temperature for 240 min, then stopping heating and naturally cooling to room temperature to obtain a product system;

[0068] (3) The product system was mixed and diluted with water in a volume ratio of 1:1, and then centrifuged at 3600 rpm for 30 min. The upper clear liquid was poured off, and the lower solid phase precipitate was washed with deionized water and ethanol and dried to obtain copper nanowires (denoted as S4).

[0069] The wire diameter and wire length parameters of S4 are shown in Table 1.

[0070] Example 5

[0071] (1) 4 g of copper nitrate trihydrate, 0.75 g of hexadecyltrimethylammonium chloride, 0.212 g of hexadecyltrimethylammonium bromide, and 8 g of polyvinylpyrrolidone PVP-K90 were placed in a three-necked round-bottom flask filled with ethylene glycol, stirred until completely dissolved, and then 1 ml of hydrazine hydrate was added, and stirring was continued to obtain a uniform mixed solution;

[0072] The feed amounts of the above raw materials satisfy the following conditions: in the mixed solution, the molar ratio of copper ion: chloride ion: hydrazine hydrate: polyvinyl pyrrolidone PVP-K90 is 1:0.14:1.2:4.4; the molar ratio of chloride ion: bromide ion is 4:1; the weight ratio of ethylene glycol: polyvinyl pyrrolidone PVP is 68:1;

[0073] (2) introducing nitrogen into the mixed solution, heating the mixed solution to 140° C., and maintaining the temperature for 5 min to fully remove water and oxygen, then stopping the nitrogen flow; maintaining 140° C., and conducting a synthesis reaction at the temperature for 240 min, then stopping heating and naturally cooling to room temperature to obtain a product system;

[0074] (3) The product system was mixed and diluted with water at a volume ratio of 1:1, and then centrifuged at 3600 rpm for 30 min. The upper clear liquid was poured off, and the lower solid phase precipitate was washed with deionized water and ethanol and dried to obtain copper nanowires (denoted as S5).

[0075] The wire diameter and wire length parameters of S5 are shown in Table 1.

[0076] Example 6

[0077] (1) 4 g of copper nitrate trihydrate, 0.65 g of tetrabutylammonium chloride, 0.76 g of tetrabutylammonium bromide, and 8 g of polyvinylpyrrolidone PVP-K90 were placed in a three-necked round-bottom flask filled with ethylene glycol, stirred until completely dissolved, and then 1 ml of hydrazine hydrate was added, and stirring was continued to obtain a uniform mixed solution;

[0078] The feed amounts of the above raw materials satisfy the following conditions: in the mixed solution, the molar ratio of copper ion: bromide ion: hydrazine hydrate: polyvinyl pyrrolidone PVP-K90 is 1:0.14:1.2:4.4; the molar ratio of chloride ion: bromide ion is 1:1; the weight ratio of ethylene glycol: polyvinyl pyrrolidone PVP is 68:1;

[0079] (2) introducing nitrogen into the mixed solution, heating the mixed solution to 150° C., and maintaining the temperature for 5 min to fully remove water and oxygen, then stopping the nitrogen flow; maintaining the temperature at 150° C. and conducting a synthesis reaction at the temperature for 240 min, then stopping heating and naturally cooling the mixed solution to room temperature to obtain a product system;

[0080] (3) The product system was mixed and diluted with water at a volume ratio of 1:1, and then centrifuged at 3600 rpm for 30 min. The upper clear liquid was poured off, and the lower solid phase precipitate was washed with deionized water and ethanol and dried to obtain copper nanowires (denoted as S6).

[0081] The wire diameter and wire length parameters of S6 are shown in Table 1.

[0082] Comparative Example 1

[0083] (1) 4 g of copper nitrate trihydrate, 0.094 g of hexadecyltrimethylammonium chloride, 1.7 g of hexadecyltrimethylammonium bromide, and 8 g of polyvinylpyrrolidone PVP-K90 were placed in a three-necked round-bottom flask filled with ethylene glycol, stirred until completely dissolved, and then 1 ml of hydrazine hydrate was added, and stirring was continued to obtain a uniform mixed solution;

[0084] The feed amounts of the above raw materials satisfy the following conditions: in the mixed solution, the molar ratio of copper ion: chloride ion: hydrazine hydrate: polyvinyl pyrrolidone PVP-K90 is 1:0.0175:1.2:4.4; the molar ratio of chloride ion: bromide ion is 0.0625:1; the weight ratio of ethylene glycol: polyvinyl pyrrolidone PVP is 68:1;

[0085] (2) introducing nitrogen into the mixed solution, heating the mixed solution to 140° C., and maintaining the temperature for 5 min to fully remove water and oxygen, then stopping the nitrogen flow; maintaining 140° C., and conducting a synthesis reaction at the temperature for 240 min, then stopping heating and naturally cooling to room temperature to obtain a product system;

[0086] (3) The product system was mixed and diluted with water in a volume ratio of 1:1, and then centrifuged at 3600 rpm for 30 min. The upper clear liquid was poured off, and the lower solid phase precipitate was washed with deionized water and ethanol and dried to obtain copper nanowires (denoted as D1).

[0087] The wire diameter and length parameters of D1 are shown in Table 1.

[0088] Comparative Example 2

[0089] (1) 4 g of copper nitrate trihydrate, 2.25 g of hexadecyltrimethylammonium chloride, and 8 g of polyvinylpyrrolidone PVP-K90 were placed in a three-necked round-bottom flask filled with ethylene glycol, and after stirring until completely dissolved, 1 ml of hydrazine hydrate was added and continued stirring to obtain a uniform mixed solution;

[0090] The feed amounts of the above raw materials satisfy the following conditions: in the mixed solution, the molar ratio of copper ion: chloride ion: hydrazine hydrate: polyvinyl pyrrolidone PVP-K90 is 1:0.42:1.2:4.4; the weight ratio of ethylene glycol: polyvinyl pyrrolidone PVP is 68:1;

[0091] (2) introducing nitrogen into the mixed solution, heating the mixed solution to 140° C., and maintaining the temperature for 5 min to fully remove water and oxygen, then stopping the nitrogen flow; maintaining 140° C., and conducting a synthesis reaction at the temperature for 240 min, then stopping heating and naturally cooling to room temperature to obtain a product system;

[0092] (3) The product system was mixed and diluted with water at a volume ratio of 1:1, and then centrifuged at 3600 rpm for 30 min. The upper clear liquid was poured off, and the lower solid phase precipitate was washed with deionized water and ethanol and dried to obtain copper nanowires (denoted as D2).

[0093] The wire diameter and length parameters of D2 are shown in Table 1.

[0094] Comparative Example 3

[0095] (1) 4 g of copper nitrate trihydrate, 1.7 g of hexadecyltrimethylammonium bromide, and 8 g of polyvinylpyrrolidone PVP-K90 were placed in a three-necked round-bottom flask filled with ethylene glycol, and after stirring until completely dissolved, 1 ml of hydrazine hydrate was added and continued stirring to obtain a uniform mixed solution;

[0096] The feed amounts of the above raw materials satisfy the following conditions: in the mixed solution, the molar ratio of copper ion: bromide ion: hydrazine hydrate: polyvinyl pyrrolidone PVP-K90 is 1:0.28:1.2:4.4; the weight ratio of ethylene glycol: polyvinyl pyrrolidone PVP is 68:1;

[0097] (2) introducing nitrogen into the mixed solution, heating the mixed solution to 140° C., and maintaining the temperature for 5 min to fully remove water and oxygen, then stopping the nitrogen flow; maintaining the temperature at 140° C. and conducting the synthesis reaction for 2 h, then stopping heating and naturally cooling the mixed solution to room temperature to obtain a product system;

[0098] (3) The product system was mixed and diluted with water at a volume ratio of 1:1, and then centrifuged at 3600 rpm for 30 min. The upper clear liquid was poured off, and the lower solid phase precipitate was washed with deionized water and ethanol and dried to obtain copper nanowires (denoted as D3).

[0099] The wire diameter and length parameters of D3 are shown in Table 1.

[0100] Table 1

[0101] Copper nanowires Wire diameter / nm Line length / μm S1 15 15 S2 20 25 S3 30 40 S4 12 10 S5 35 30 S6 30 10 D1 No copper nanowires were formed No copper nanowires were formed D2 100 10 D3 No copper nanowires were formed No copper nanowires were formed

[0102] As can be seen from Table 1, the method of the present invention can produce ultrafine copper nanowires with a diameter of 12-35nm and a length of 10-40μm. During the preparation process, as the molar ratio of chloride ions to bromide ions in the synthesis system decreases, the diameter of the synthesized copper nanowires shows a trend of decreasing. In addition, the chlorine-bromine ratio used in Comparative Example 1 is too low, and Comparative Example 3 does not use chlorine-containing compounds, and copper nanowire products cannot be obtained. Comparative Example 2 does not use bromine-containing compounds, and the synthesized copper nanowires cannot meet the index requirements of the ultrafine copper nanowires of this application.

[0103] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A method for preparing copper nanowires, characterized in that: The method comprises: (1) mixing a copper source, a chlorine-containing compound, a bromine-containing compound, a protective agent, a polyol and a reducing agent to obtain a mixed solution; (2) subjecting the mixed solution to a synthesis reaction to obtain a product system; (3) separating the product system and post-treating the separated solid phase to obtain copper nanowires; wherein: In the mixed solution, the molar ratio of copper ion: chloride ion: reducing agent: protecting agent is 1: (0.01-1): (0.1-3): (1-8); The molar ratio of chloride ion: bromide ion is (0.25-4):1; The conditions of the synthesis reaction include: temperature of 120-180°C and time of 30-300 min; The copper nanowire has a diameter of 12-35 nm and a length of 10-40 μm.

2. The method according to claim 1, wherein: The copper source is selected from at least one of copper nitrate, copper carboxylate, copper sulfate, copper acetylacetonate, copper acetate and copper chloride.

3. The method according to claim 1 or 2, wherein: The chlorine-containing compound is selected from at least one of hexadecyltrimethylammonium chloride, octadecyltrimethylammonium chloride, tetrapropylammonium chloride and tetrabutylammonium chloride; And / or, the bromine-containing compound is at least one selected from hexadecyltrimethylammonium bromide, octadecyltrimethylammonium bromide, tetrapropylammonium bromide and tetrabutylammonium bromide.

4. The method according to claim 3, wherein: The chlorine-containing compound is hexadecyltrimethylammonium chloride; And / or, the bromine-containing compound is hexadecyltrimethylammonium bromide.

5. The method according to claim 1 or 2, wherein: The protective agent is selected from at least one of polyvinyl pyrrolidone, nitrogen methyl pyrrolidone, hexadecylamine and polyvinyl alcohol; And / or, the polyol is selected from at least one of ethylene glycol, propylene glycol and glycerol.

6. The method according to claim 5, wherein: The protective agent is selected from polyvinyl pyrrolidone.

7. The method according to claim 1 or 2, wherein: The reducing agent is selected from at least one of hydrazine hydrate, potassium borohydride, sodium borohydride and ferric sulfate.

8. The method according to claim 7, wherein: The reducing agent is hydrazine hydrate.

9. The method according to claim 1 or 2, wherein: In step (1), the feed amount of each raw material is such that, in the mixed solution, the molar ratio of copper ion: chloride ion: reducing agent: protecting agent is 1: (0.05-0.3): (1-3): (4-6).

10. The method according to claim 1, wherein: In step (1), the molar ratio of chloride ion:bromide ion is (0.5-2):

1.

11. The method according to claim 1 or 2, wherein: In step (2), the conditions of the synthesis reaction include: temperature of 140-150° C.; time of 240-300 min.

12. The method according to claim 1 or 2, wherein: The method further comprises: before the synthesis reaction, heating the mixed solution in an inert atmosphere to remove water and oxygen.

13. The method according to claim 12, wherein: The conditions of the heating treatment include: a temperature of 135-150° C. and a time of 1-10 min.

14. The method according to claim 1 or 2, wherein: The post-treatment includes washing and drying in sequence.

15. The copper nanowire prepared by the method according to any one of claims 1 to 14, wherein: The copper nanowire has a diameter of 12-35 nm and a length of 10-40 μm.

16. Use of the copper nanowires according to claim 15 in flexible conductive materials and transparent conductive films.

Citation Information

Patent Citations

  • Preparation method of copper nano material structure

    CN111906329A

  • Synthesis method of ultra-pure copper nanowire

    CN114603130A